An Examination of Adherence to Pain Medication Plans in Older Cancer Patients in Hospice Care - Sanders, Sara (2012)
CONTEXT: Timely and appropriate management of pain is essential to promote comfort at the end of life. OBJECTIVES: To determine if pain-related factors and non-pharmacological interventions affect medication adherence in older cancer patients in community-based hospices. METHODS: The study involved cancer patients 55 years and older, newly admitted to one of 13 community-based hospices in the Midwest U.S. A descriptive design with patients or their proxies providing information during two telephone interviews and review of their hospice medical records was used. RESULTS: A total sample of 65 patients was obtained, with data directly from 32 patients during interview one (T(1)); 25 at interview two (T(2)), and proxy reports for 33 (T(1)) and 30 (T(2)) patients. The overall mean pain medication adherence scores (maximum 9) for all patients were 8.43 (T(1)) and 8.38 (T(2)). For component analysis (three components; maximum of three points each), patients were the least adherent with opioid orders at both time points (2.65). Patients were the most adherent to nonsteroidal anti-inflammatory/acetaminophen orders at T(1) (2.91) and to medications for neuropathic pain at T(2) (2.89). Data provided statistical evidence that patients with more hours of controlled pain in the past 24 hours were more likely to have had better adherence, whereas patients with higher levels of comfort over the last few days were more likely to have had worse adherence. CONCLUSION: This study identified that pain medication adherence among older adults with cancer receiving hospice care is high. However, hospices must be alert to the fact that even as patients become more comfortable, adherence must continue to be emphasized to ensure pain does not re-develop or exacerbate, if pain relief is a patient priority.